Use of phosphonate to manage foliar potato late blight in developing countries - Kromann, P.; Pérez, W.; Taipe, A.; Schulte-Geldermann, Elmar; Sharma, B.P.; Andrade-Piedra, J.L.; Forbes, G. (Scientific Societies, 2012)
Twenty phosphonate products found in the agrochemical market in Ecuador and Peru were evaluated in bioassays for the control of foliar potato late blight, caused by Phytophthora infestans. Eight phosphonate products were evaluated in 16 field experiments done in Peru, Ecuador, Kenya, and Nepal. A meta-analysis across locations involving 71 combinations of potato genotype by site and year demonstrated a significant relationship between phosphonate application rate and efficacy for controlling late blight on potato foliage. The meta-analysis revealed that phosphonate rates of approximately 2.5 g a.i./liter provided efficacy similar to that of the conventional contact fungicides mancozeb and chlorothalonil used at similar rates. At rates higher than 2.5 g a.i./liter, the efficacy of phosphonate was superior to the contact fungicides. Overall, late blight control by phosphonate appeared relatively stable in field experiments across locations. An analysis of field experiments and 64 combinations of potato genotype by site and year showed no correlation between the susceptibility level of potato genotypes and efficacy of phosphonates. The cost of both phosphonate compounds and contact fungicides varied greatly among the countries of the field study; however, in Kenya, control with phosphonate was clearly less expensive than with mancozeb.